Campaigns and Political Marketing - Wayne P. Steger, Sean Q Kelly, dkk (The Haworth Press, 2006)
Over the past few years political marketing strategies have been refined with the help of new findings in political science research. Campaigns and Political Marketing clearly discusses the most recent political science research studies and theories that political activists and professionals can apply to effectively campaign for an issue or candidate. This text is an invaluable compilation of research, theory, and practical application from political science experts across the country that guides readers through the complexities of everyday political marketing and campaigning. Readers get the critical knowledge needed on how to best affect public viewpoints and gain the strongest advantage over the opposition.